2020
DOI: 10.15252/embj.2020107407
|View full text |Cite
|
Sign up to set email alerts
|

Membrane protein biogenesis by the EMC

Abstract: The endoplasmic reticulum (ER) membrane protein complex (EMC) was identified over a decade ago in a genetic screen for ER protein homeostasis. The EMC inserts transmembrane domains (TMDs) with limited hydrophobicity. Two recent cryo‐EM structures, and a third model based on partial high‐ and low‐resolution structures, suggest how this is accomplished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…However, the Emc6–Emc3 core region with their 6 transmembrane domains are sufficient to promote protein insertion. This observation confirms the insertion mechanism that was proposed on the basis of recent cryo-electron microscopic studies that revealed that a membrane-embedded hydrophobic groove formed by Emc3 and Emc6 constitutes a transient binding site that incorporates transmembrane stretches into a disturbed and locally thinned lipid bilayer [ 35 37 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 87%
“…However, the Emc6–Emc3 core region with their 6 transmembrane domains are sufficient to promote protein insertion. This observation confirms the insertion mechanism that was proposed on the basis of recent cryo-electron microscopic studies that revealed that a membrane-embedded hydrophobic groove formed by Emc3 and Emc6 constitutes a transient binding site that incorporates transmembrane stretches into a disturbed and locally thinned lipid bilayer [ 35 37 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 87%
“…Extracts were produced by solubilising membranes with the detergent dodecyl-maltoside (DDM) and subsequently fractionated by size exclusion chromatography. We know from previous findings that cardiolipin (CL) is required to stabilise the associated states of SecYEG-SecDFyajC-YidC (the holo-translocon) as well as the holo-translocon-BAM super-complex [1719], so we reasoned that if an even larger Sec-associated complexes existed in the envelope then they too would be stabilised by CL. Thus, the size-exclusion experiments were conducted with and without augmented CL in the column buffer (0.02 % (w/v) DDM ± 0.002 % (w/v) CL).…”
Section: Resultsmentioning
confidence: 99%
“…Simulations on the S . cerevisiae EMC structure have revealed that perturbations in the cytoplasmic leaflet of the ER bilayer facilitates flooding of the substrate binding pocket with water, promoting a hydrophilic environment instrumental to insertion [ 51 ]. Since PC and PE are major structural components of the ER membrane, it is tempting to speculate that the role of the TbEMC in lipid biosynthesis may be tied to the creation of a microenvironment conducive to TMD insertion, and thus TbEMC function.…”
Section: Discussionmentioning
confidence: 99%